The impact of platelet indices on ischemic stroke: a Mendelian randomization study and mediation analysis - Li, Yang; Xiang, Wenping; Xue, Hui; Meng, Tianyu; Zhang, Tianyou; Zhang, Jinfeng; Wang, Jingbo; Zhao, Jili; Wang, Baojun (Frontiers in Neurology, 2023)
Introduction: Platelet indices (PIs) are hematological parameters that indicate the number, morphology, and activation of platelets. Although some clinical trials suggest an association between PIs and risk of stroke, the lack of robust evidence is attributed to confounding effects and reverse causation. Objective: This study aims to evaluate the association between PIs and stroke risk through Mendelian randomization (MR), while exploring the mediating effect of blood pressure in this association. Methods: We identified genetic variants associated with PIs, including platelet count (PLT), platelet distribution width (PDW), mean platelet volume (MPV), and platelet crit (PCT), in the UK Biobank (n = 350,474). Relevant genome-wide association studies were utilized to gather summary statistics pertaining to the traits of interest. We primarily used the inverse-variance weighted analysis to obtain estimates for individual causal power.Result: We observed a positive correlation between genetically predicted increases in PCT levels with stroke onset (PCT: OR (95%CI) = 1.113(1.047, 1.183), P < 0.001).However, no significant causal relationship was found between PLT, PDW, and MPV and the risk of stroke (PLT: OR (95%CI) = 1.037(0.979, 1.098), P = 0.221; PDW: OR (95%CI) = 0.973(0.923, 1.024), P = 0.294; MPV: OR (95%CI) = 0.990(0.945, 1.038), P = 0.675). Besides, multivariable MR analyses and mediation analysis found that the proportion mediated by systolic blood pressure (SBP) is 23.71% (95%CI (10.85%-33.31%)) and the proportion mediated by diastolic blood pressure (DBP) is 28.09% (95%CI (12.92%-39.63%)). Conclusion: This large MR study present evidence for the potential causal relationship between PCT level and the risk of ischemic stroke, which might be mediated by blood pressure.